Implementasi Program Edukasi Lingkungan Untuk Mengurangi Penggunaan Plastik Di Sekolah Dasar - Muhamad Wahyudin; Ulfa Ni’matus Sa’adah; Faiz Faricha (Impact: Jurnal Pengabdian kepada Masyarakat, 2024)
The use of single-use plastics in the school environment is still a significant problem in environmental conservation efforts. Elementary schools as educational institutions have an important role in shaping environmental awareness from an early age through structured educational programmes. This study aims to evaluate the implementation of the environmental education programme in reducing plastic use at SDN Blora, as well as identify the supporting and inhibiting factors in its implementation. This research uses the Community Engagement Research (CRE) method with a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation and document analysis. The research informants consisted of principals, teachers, students, and parents of students involved in the environmental education programme. The results showed that the environmental education programme has successfully reduced the use of single-use plastics in schools. The implementation of school policies, active participation of students in waste sorting and recycling activities, and parental support were the main factors for the success of the programme. However, some challenges such as limited resources and resistance to habit change are still found. To overcome these challenges, it is necessary to strengthen policies, increase socialisation to parents, and implement a reward system for students who are active in the programme.